DEKONSTRUKSI AKUNTANSI: PERAN AKUNTANSI DALAM MEMBANGUN PERADABAN (KRITIK TERHADAP AKUNTANSI TRADISIONAL) - Toni Adhitya; Ruston Nawawi (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2018)
The new accounting history paradigm in accounting history studies generally criticizes the approach used by traditional accounting history which is said to be ahistorical and antiquated. It is said to be ahistorical because accounting history is written with a present point of view, where accounting history tends to be presented chronologically by slowly displaying current truths. And it is said to be antique because the history of accounting is concentrated on the explanation of